Bromeliaceae endémicas del Perú - León, Blanca (2006)
The Bromeliaceae are recognized in Peru with 19 genera and approximately 450 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all epiphytic or terrestrial herbs. Here we recognize 223 endemic taxa in 13 genera. We assigned IUCN threat categories to 161 taxa. Three genera, Pitcairnia, Puya and Tillandsia, encompass the majority of Peruvian endemics in this family. The endemic taxa are found in a wide range of ecological regions, from Pluvial Montane Forest to Lowland Amazonian Forest on the eastern side of the country to the Mesoandean, and Dry and Humid Puna on the western side, between 100 and 4700 m elevation. Approximately half of the endemic species are known from a single locality, reflecting insufficient exploration of the regions where the family is diverse, and the lack of a specialist in the country. Twenty-one species endemic to Peru have been registered to date in the country’s protected areas network.